RELIGIUSITAS REMAJA: STUD1 TENTANG KEHIDUPAN BERAGAMA DI DAERAH ISTIMEWA YOGYAKARTA - Afiatin, Tina (Faculty of Psychology, Universitas Gadjah Mada, 1998)
Discrepancy between intensive religious study and manifestation of religious life is a phenomenon happens among teenagers in Indonesia including those of the Special District of Yogvakarra. In this district, the Javanese is the majority of its population. The purpose of this research is to explore the degree of religious conscience and some dominant factors influencing religious life of the teenagers in the Special District of 1'0 9akarta. The quantitative and qualitative approaches are applied in this research. The respondents ofthe research are the Islamic students of Junior and Senior High School in the Special District of Yogyakarta. The number of all respondents are 441. Thirty four respondents attend a Focused Group Disczrssion and four respondents are intervielved in depth and observed in order to knortj their religious background. The result of the study shows that the highest dimension degree of the religious dimension is the ritual one, however, it is not foNowed by the other dimensions. The result of qualitative analysis sho vs that the implementation of ritual religion is not suflciently supported 6). adequate internalization of the belief and knowledge. Furthermore, it is conclzrded that the religious education in the school, focuses more on the cognitive rather than the affective, attitude and spiritual domains. Some factors rnfllret7cing the religious life of the teenagers are parents' attention and consistencj. in guiding them on religious practice and the new inhabitants around the respondents in prosel.vtizing Islamic religion activity. Besides, the peer group, the key persons in the community and the mass media are regarded as havingpositive contribution to religious life for teenagers.